Sleep Patterns and its influence on Sleep Problems among Children in India: A Systematic Review & Meta-Analysis (Indian Journal of Public Health Research & Development, 2020)
Sleep is equally important to the food we eat, the liquids we drink, or the safety of the children. Eachliving being needs sleep. It is the essential activity of the mind during each stage of development. Whereasinadequate sleep can lead to the development of various health issues. Although a generous group ofliterature has explored the relationship between sleep patterns and problems, comprehensive reviews andfar-reaching conclusions are lacking. This systematic review was conducted to describe the sleep pattern orhabits present in Children and also to identify its influence on the onset of various sleep problems among 3to 18 years. Electronic databases were searched for articles published up to August 2019 and no limits forstudy designs were kept. The articles for review were obtained from databases like MEDLINE, PubMed,Cochrane, and Google Scholar along with a handful of references of experts using Boolean operators’ searchcriteria. The guidelines adopted were Preferred Reporting Items for Systematic Reviews and Meta-Analyses(PRISMA). The nighttime sleep duration was the most common sleep measure or variable in 73% of thearticles. The average sleep duration (night time) is 9.811 hours (3 to 5 years), 9.082 hours (6 to12 years)and 7.944 hours (12 to 18 years). The result from this review suggested that sleep patterns tend to delay asthe age increases leading to insufficient sleep and irregular bedtime schedules leading to the onset of someof the sleep problems like snoring, nightmare, bedwetting, etc. A few reviews suggested that it was difficultto define the sleep problem effectively as families vary greatly in their tolerance of their children’s sleepinghabits.
Keywords: Sleep, Sleep Pattern, Sleep Problems, Children’s Sleep